Form and 'englishness' in the poems of the William Shakespeare - Jonid, Tanja
This study examines Shakespeare's use of form in expressing 'Englishness' in his poems, not only in terms of the poetic or stanzaic forms employed but also through the use of such poetic devices as rhyme, alliteration and rhythm. The research was conducted based on the theory of historical formalism proposed by Stephen Cohen, which applies the combined approaches of new historicism and formalism. The first two chapters introduce the study through providing the literature review and explaining the theory and methodology used for the analysis. The discussion chapters (Chapters 3 to 6) deal with all the poems of William Shakespeare, and are organized according to the commonly-accepted chronology, beginning with the Sonnets, followed by Shakespeare's two long narrative poems, and ending with an analysis of a shorter poem, “The Phoenix and the Turtle”. The analysis focuses on ten sonnets selected because of their formal and thematic divergence from the sonnet tradition, as well as their relevance to the other poems analysed in this thesis. The thesis then examines how the sonnet form was appropriated and transformed by Shakespeare, and expresses 'Englishness'. A closer look is taken at how the formal elements in the narrative poems Venus and Adonis and The Rape of Lucrece articulate 'Englishness' even while they treat classical subjects. It is found that 'Englishness' is expressed through reinvention and reversals reflective of developments in Shakespeare's own life as well as the historical developments in England in his time. Analysis of a later poem by Shakespeare, “The Phoenix and the Turtle”, shows how this poem displays obvious references not only to the work of the great medieval English poet Geoffrey Chaucer but also to the tradition of alliterative poetry of the imagined ancient ancestors of the English, the Anglo-Saxons, in an apparent effort to express an overt 'English' character, or 'Englishness'. This thesis attempts to employ Stephen Cohen's historical formalism to uncover what it is in Shakespeare's poetry that justifies his works as being seen to represent 'Englishness'.